Metamorphosis of the Student’s Role in Modern Pedagogy - Gagoshidze, Tamar (European Scientific Journal, ESJ, 2025)
Characterizing today’s student is a complex and challenging task, as the profiles, experiences, and educational paths of modern youth are highly diverse. Over the past decade, the heterogeneity of the population has significantly increased. Notably, within the university walls, we now have a diverse community with various educational backgrounds-professionally trained individuals, recent graduates, international students, working students, and so forth. This new, composite student population, with its socio-demographic characteristics, has moved away from the “traditional” ideal figure of a school graduate and increasingly demands new approaches. In this paper, we will attempt to introduce the historical path that pedagogy has taken and illustrate how the student of a past era transformed into the modern student. To demonstrate this transformation, we will rely on empirical, comparative, and quantitative scientific research.